"Auditoria de gestión y su relación con el desarrollo administrativo y operacional de la cooperativa de taxis rey cantón Quevedo. año 2012 - Martínez Nieves, Danny Damián (2015)
This research was conducted to know the effect of the The Audit Management and its Relationship to Operational Administrative Development Cooperative Taxis REY. For the development of this research, the inductive, deductive and analytical methods used - synthetic which allowed me to study establishing facts through observation, analysis and classification of the information obtained for the conclusion of the problem, for it was applied a survey of members and interview the manager of the cooperative, valuable information which contributed largely to carry out this work. Taxis Cooperative KING recent years its expansion has been steady, providing quality service and continuous improvement. But the lack of a Management Audit has caused difficulties in the administration and operation of the Cooperative Taxi company REY affecting compliance with the objectives set in the short, medium and long term. To achieve the objectives of this work were followed the following strategies: • Diagnose the internal control procedure using Taxis Cooperative REY. • Analyze the administrative management system and operational • Propose a manual internal control in order to improve the operational management in business development of the Cooperative Taxi REY.